Legal Review Of Liability From Deepfake Artificial Intelligence That Contains Pornography - Muhammad Ilman Abidin (MIMBAR : Jurnal Sosial dan Pembangunan, 2023)
This article seeks to determine who is responsible for the widespread use of deepfake AI to create pornographic content and how Indonesian law governs it. Deepfakes, a subfield of artificial intelligence, can manipulate visual media by superimposing facial features on the bodies of others, creating misleading videos. Deepfakes were first used in movies and then in gadgets. However, deepfakes have been used to make explicit pornographic videos. This research is normative law-based. This study found that Indonesia has no specific legislation on artificial intelligence technology, except for Law Number 19 of 2016, which amends Law Number 11 of 2008 on Electronic Information and Transactions. Number 44 of 2008 on Pornography prohibits pornographic content creation and provides criminal penalties to hold offenders accountable. In Government Regulation (PP) Number 71 of 2019, which regulates electronic systems and transactions, pornographic platform providers cannot use deepfake technology.